Adaptive Governance at Correctional Institution Class IIB Nunukan Inmate Development Program: JEL Classification: H83, K42, J24 - Puang Dirham; Muh. Akmal Ibrahim; Hasniati Hasniati; Didik Iskandar (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
To improve the skill of inmates, the Nunukan Class IIB Correctional Institution makes coaching program that is expected to be way for inmates to improve their abilities. in order to make the program success, adaptation from the Correctional Institution is needed. This research tries to explore further how the Correctional Institution adjusts and is adaptive in fostering prisoners in the Nunukan class IIB prison, especially from the aspect of Adaptive Governance. Adaptive governance includes adaptive capacity, Polycentric Institutions, Public Participation/Input, Social Learning, Bridging Organizations and Multilevel Networks. The data is then compiled in qualitative research. Data collection methods include observation, interviews and documentation. Data sources consist of primary and secondary data, data analysis with interactive methods. The results of this study show that Lapas IIB Nunukan has implemented adaptive governance, but adaptive capacity has not been optimized. There is still a need to strengthen formal networks, increase human resource capacity, and cross-actor collaboration to be truly adaptive and sustainable.